Unpublished Cuneiform Texts in the Iraqi Museum TIM-5 Series - Meadhad, Ali Hashim (Al-Adab Journal, 2022)
Text No. (1 = TIM5,14). Legal text - “Seven people (workers) went out to fetch their shares of (bran), and they were found killed by weapons, so their shares were not handed over to the person responsible for receiving the rations, and instead of them, seven other strong workers went and fetched their shares of bran.” The text states that the daily work in the past was not without problems facing its workers, and it seems that the looting and appropriation of the property of others, which sometimes amount to committing the crime of murder, is one of the issues that occurred in the old Iraqi society, and these cases are known and occur even in Our present societies are among the common crimes committed.Text No. (2 = TIM5,69). Administrative text - representing the assignment of numbers of men to work in different locations, (3 in the bar), (3 at the threshold of the restored bridge), (3 in the temple of the god Dumuzi), (5 people in the city of Zamore) and (4 people in the temple) and others.Text No. (3 = TIM,70). Administrative text - related to the army, consisting of assigning soldiers to serve in different cities (1 attributed to the city’s “governor”), (1 attributed to the city of Babylon), (2 to the city of Larsa)), 1 to the city of Warka), (1 to the city of Isani), (1 to the city of Rabiqom).